Tantangan Dakwah Menghadapi Arogansi Intelektual dalam Perpektif Al-Quran - Budi Utomo (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2023)
Scholars and preachers are nevertheless capable of intellectual arrogance. The purpose of this essay is to disclose a study of the interpretation of verses that discuss Intellectual Arrogance and how the answers are presented in the Qur'an. The approach employed is the method of comparative interpretation (muqarin), which derives from authoritative commentary books, and includes both history-based (bi al-matsur) and ratio-based (bi al-ra'yi) interpretations. This research's findings suggest that the Qur'an contains a study of intellectual arrogance, which is a terrible character to avoid. Apart from that, it gives instruction and ways to overcome intellectual arrogance. The study's findings also promote scientific ideals and morality in Indonesian Muslim academics, including preachers so that they can behave properly and proportionally in the world of academia and preaching.